2022
DOI: 10.3389/fimmu.2022.866319
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Progression of Cutaneous Lupus to Systemic Lupus Erythematosus

Abstract: Lupus erythematosus is an autoimmune disease that may manifest in a variety of organs and tissues including the skin, kidney, brain, heart and lung. Many patients present with cutaneous lupus, where disease is often limited to the skin, but are at risk for developing systemic lupus. The objective of our present study is to perform a systematic review of studies that investigated patient cohorts and populations for the occurrence of cutaneous lupus progressing to systemic lupus. Inclusion criteria required that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
1
10
0
2
Order By: Relevance
“…In a systematic review, a broad range of progression rates from cutaneous lupus to SLE was reported, ranging from 0% to 42% in adult studies, and 0%–31% in pediatric studies. 90 Discoid lupus followed by subacute cutaneous lupus was the most common cutaneous lupus subtypes studied. Time to progression was informed inconsistently among studies and ranged from 5.6 months to 8.2 years in adult studies.…”
Section: Clinical Autoimmune Entities and Risk Of Developing Slementioning
confidence: 97%
See 2 more Smart Citations
“…In a systematic review, a broad range of progression rates from cutaneous lupus to SLE was reported, ranging from 0% to 42% in adult studies, and 0%–31% in pediatric studies. 90 Discoid lupus followed by subacute cutaneous lupus was the most common cutaneous lupus subtypes studied. Time to progression was informed inconsistently among studies and ranged from 5.6 months to 8.2 years in adult studies.…”
Section: Clinical Autoimmune Entities and Risk Of Developing Slementioning
confidence: 97%
“…Time to progression was informed inconsistently among studies and ranged from 5.6 months to 8.2 years in adult studies. 90 Rates of progression may vary according to the classification criteria used for SLE. For example, in a single center, historical, medical records review study of 93 patients with cutaneous lupus, 10.8% progressed to SLE under the SLICC criteria, whereas 16.1% did so under the ACR criteria.…”
Section: Clinical Autoimmune Entities and Risk Of Developing Slementioning
confidence: 99%
See 1 more Smart Citation
“…The risk for progression to SLE in DLE patients is estimated between 5 and 30%. The generalized form of DLE has a higher potential of progressing to SLE compared to those with localized lesions (12,(19)(20)(21)(22). Potential risk factors for progression to systemic disease are suggested to be anemia, arthritis and positivity for ANA (19).…”
Section: Association To Slementioning
confidence: 99%
“…Cutaneous lupus erythematosus (CLE) is an autoimmune disorder associated with a broad spectrum of cutaneous manifestations. It may progress into systemic lupus erythematosus (SLE) and involve multiple organ systems ( 1 ). CLE can be further classified into acute, subacute, or chronic subtypes according to the clinical characteristics of the skin lesions ( 2 ).…”
Section: Introductionmentioning
confidence: 99%